Cbl-Associated Protein CAP contributes to correct formation and robust function of the Drosophila heart tube - Jammrath, Jennifer; Reim, Ingolf; Saumweber, Harald (PLoS ONE, 2020)
The formation of a tube-like structure is a basic step in the making of functional hearts in vertebrates and invertebrates and therefore, its understanding provides important information on heart development and function. In Drosophila, the cardiac tube originates from two bilateral rows of dorsally migrating cells. On meeting at the dorsal midline, coordinated changes in cell shape and adhesive properties transform the two sheets of cells into a linear tube. ECM and transmembrane proteins linked to the cytoskeleton play an important role during these dynamic processes. Here we characterize the requirement of Cbl-Associated Protein (CAP) in Drosophila heart formation. In embryos, CAP is expressed in late migrating cardioblasts and is located preferentially at their luminal and abluminal periphery. CAP mutations result in irregular cardioblast alignment and imprecisely controlled cardioblast numbers. Furthermore, CAP mutant embryos show a strongly reduced heart lumen and an aberrant shape of lumen forming cardioblasts. Analysis of double heterozygous animals reveals a genetic interaction of CAP with Integrin-and Talin-encoding genes. In post-embryonic stages, CAP closely colocalizes with Integrin near Z-bands and at cell-cell contact sites. CAP mutants exhibit a reduced contractility in larval hearts and show a locally disrupted morphology, which correlates with a reduced pumping efficiency. Our observations imply a function of CAP in linking Integrin signaling with the actin cytoskeleton. As a modulator of the cytoskeleton, CAP is involved in the establishment of proper cell shapes during cardioblast alignment and cardiac lumen formation in the Drosophila embryo. Furthermore, CAP is required for correct heart function throughout development.
CRIS-Team Scopus Importer:2020-06-16